2022
DOI: 10.1186/s12889-022-13195-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 restrictions on perceived health and wellbeing of adult Australian sport and physical activity participants

Abstract: Individuals’ access to sport and physical activity has been hampered due to COVID-19 lockdown restrictions. In Australia participation in community sport was cancelled during lockdowns. There is limited research on the impact of sport participation restrictions on the health and wellbeing of adults.AimThe aim of this study was to investigate the perceived health and wellbeing of a sample of predominantly active Australian adults, both during COVID-19 and in comparison with one year earlier (pre COVID-19).Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
(50 reference statements)
1
14
0
Order By: Relevance
“…Finally, the statistical analyses showed that athletes aged between 18 and 35 obtained the lowest average level of well-being ( = 60.20/100). This result is consistent with the finding obtained in the study of Rochelle et al [ 25 ], which show that among Australians, the younger age cohort (18–29 years) reported significantly poorer general well-being during the pandemic than the older age groups. In addition, the level of psychological well-being was significantly higher among young athletes between 3 and 12 years of age than for all other age groups.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the statistical analyses showed that athletes aged between 18 and 35 obtained the lowest average level of well-being ( = 60.20/100). This result is consistent with the finding obtained in the study of Rochelle et al [ 25 ], which show that among Australians, the younger age cohort (18–29 years) reported significantly poorer general well-being during the pandemic than the older age groups. In addition, the level of psychological well-being was significantly higher among young athletes between 3 and 12 years of age than for all other age groups.…”
Section: Discussionsupporting
confidence: 93%
“…Stanton et al [9] reported that almost half of their respondents reported a reduction in physical activity since the onset of the COVID-19 pandemic, but about 20% also reported a positive change. Probable reasons for lower levels of physical activity during the lockdown include the closure of usual exercise venues, social distancing, the cessation of club and community sport and an unwillingness to change previous exercise habits; all of which have been offered previously by studies [9,25].…”
Section: Discussionmentioning
confidence: 99%
“…Commenting on patterns in PA, Eime et al . ( Eime et al , 2022 ) suggest that COVID-19 restrictions negatively impacted PA for individuals who already led a primarily sedentary lifestyle but that the pandemic supported some individuals to prioritize PA and begin a more active life. Constandt et al .…”
Section: Introductionmentioning
confidence: 99%